2016
DOI: 10.1186/s12913-016-1807-6
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge translation intervention to enhance clinical application of a virtual reality system in stroke rehabilitation

Abstract: BackgroundDespite increasing evidence for the effectiveness of virtual reality (VR)-based therapy in stroke rehabilitation, few knowledge translation (KT) resources exist to support clinical integration. KT interventions addressing known barriers and facilitators to VR use are required. When environmental barriers to VR integration are less amenable to change, KT interventions can target modifiable barriers related to therapist knowledge and skills.MethodsA multi-faceted KT intervention was designed and implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 37 publications
2
94
0
1
Order By: Relevance
“…Levac et al [26] report findings from the current study related to changes in therapists’ knowledge and self-reported skills related to VR system use. The current study was designed to address the following question: Does participation in a KT intervention influence therapists’ confidence, clinical reasoning, and observed application of MLS during VR interventions?…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Levac et al [26] report findings from the current study related to changes in therapists’ knowledge and self-reported skills related to VR system use. The current study was designed to address the following question: Does participation in a KT intervention influence therapists’ confidence, clinical reasoning, and observed application of MLS during VR interventions?…”
Section: Introductionmentioning
confidence: 61%
“…Therapists were expected to become proficient at understanding the VR system, its games and its technical operation [26] in addition to reviewing MLS knowledge and adapting MLS use to this approach. The KT intervention did not include the opportunity to practice using a motor learning VR approach with a standardized client prior to implementing the IREX with therapists’ own clients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Failure to engage therapists in this way may result in discrepancies between their needs and what the technology can offer [19]. Addressing environmental and resource barriers early in the implementation process (eg, funding, treatment space requirements, location, technical and clinical personnel support, time to learn and to use) can also promote the likelihood of success [6,19]. For optimal effectiveness, KT interventions should target identified barriers and facilitators of change [36].…”
Section: Discussionmentioning
confidence: 99%